Localism and neighbourhood planning : power to the people? / edited by Sue Brownill and Quintin Bradley. - Brownill, Sue; Bradley, Quintin (Policy Press, 2017)
A critical analysis of neighbourhood planning. Setting empirical evidence from the UK against international examples, the editors engage in broader debates on the purposes of planning and the devolution of power to localities.